Specific excretion of Serratia marcescens protease through the outer membrane of Escherichia coli. - Yanagida, N (1986)
A DNA fragment of Serratia marcescens directing an extracellular serine protease (Mr, 41,000) was cloned in Escherichia coli. The cloned fragment caused specific excretion of the protease into the extracellular medium through the outer membrane of E. coli host cells in parallel with their growth. No excretion of the periplasmic enzymes of host cells occurred. The cloned fragment contained a single open reading frame of 3,135 base pairs coding a protein of 1,045 amino acids (Mr 112,000). Comparison of the 5' nucleotide sequence with the N-terminal amino acid sequence of the protease indicated the presence of a typical signal sequence. The C-terminal amino acid of the enzyme was found at position 408, as deduced from the nucleotide sequence. Artificial frameshift mutations introduced into the coding sequence for the assumed distal polypeptide after the C terminus of the protease caused complete loss of the enzyme production. It was concluded that the Serratia serine protease is produced as a 112-kilodalton proenzyme and that its N-terminal signal peptide and a large C-terminal part are processed to cause excretion of the mature protease through the outer membrane of E. coli cells.